'Keeping story alive': screening Indigenous resistance in Mitch Torres' Jandamarra's War (2011) and Keepers of the Story: Jandamarra (2010). Issue 1 (19th April 2016) - Dutto, Matteo
ABSTRACT: Stories of Indigenous resistance to colonisation were central to the Australian History wars and remain an area of contestation in Australian History. In recent years, documentaries by Indigenous directors have played a significant role in challenging orthodox histories of colonial conflict and Indigenous resistance. This paper reflects on this work by considering the production, form and style of Jandamarra's War (2011) and Keepers of the Story: Jandamarra (2010), two historical documentaries by Indigenous director Mitch Torres that retell the story of the Bunuba freedom fighter Jandamarra from what she describes as a 'Bunuba perspective'. It argues that by combining Indigenous storytelling practices with a process of textual hybridisation, Torres enacts a set of new historical practices that allows Bunuba people to reclaim Jandamarra's story as their own, indeed as a story that comes from and belongs to their country. I therefore propose to consider Torres' work not only as a new manifestation of the Jandamarra legend but as an historically significant strategic act of keeping the story of Jandamarra 'alive' by renegotiating the terms of its telling and reasserting its place in country.